Self-reported health problems and obesity predict sickness absence during a 12-month follow-up: a prospective cohort study in 21 608 employees from different industries. Issue 10 (31st October 2019) - Pihlajamäki, Minna; Uitti, Jukka; Arola, Heikki; Ollikainen, Jyrki; Korhonen, Mikko; Nummi, Tapio; Taimela, Simo
Abstract : Objectives: To study whether self-reported health problems predict sickness absence (SA) from work in employees from different industries. Methods: The results of a health risk appraisal (HRA) were combined with archival data of SA of 21 608 employees (59% female, 56% clerical). Exposure variables were self-reported health problems, labelled as 'work disability (WD) risk factors' in the HRA, presence of problems with occupational well-being and obesity. Age, socioeconomic grading and the number of SA days 12 months before the survey were treated as confounders. The outcome measure was accumulated SA days during 12-month follow-up. Data were analysed separately for males and females. A Hurdle model with negative binomial response was used to analyse zero-inflated count data of SA. Results: The HRA results predicted the number of accumulated SA days during the 12-month follow-up, regardless of occupational group and gender. The ratio of means of SA days varied between 2.7 and 4.0 among those with 'WD risk factors' and the reference category with no findings, depending on gender and occupational group. The lower limit of the 95% CI was at the lowest 2.0. In the Hurdle model, 'WD risk factors', SA days prior to the HRA and obesity were additive predictors for SA and/or the accumulated SA days in all occupational groups. Conclusion: Self-reported health problems and obesity predict a higher total count of SA days in an additive fashion. These findings have implications for both management and the healthcare system in the prevention of WD.